Youth Perspectives on Religious Education and Intercultural Respect: A Survey Analysis - Anna Halafoff; Gary D. Bouma; Mary Kalantzis (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This paper presents findings from a survey conducted among high school students to explore their views on religious education and its role in promoting intercultural respect. The survey aims to understand students' perspectives on how religious studies influence their attitudes toward different cultural and religious groups. Results show that students exposed to diverse religious teachings tend to demonstrate higher levels of tolerance and curiosity about other cultures, supporting the notion that religious education can play a critical role in fostering intercultural understanding.